INTERDISCIPLINARY PERSPECTIVES ON INDIVIDUAL CONSUMPTION DECISION - Mihaela Andreea STROE; Elena Mihaela ILIESCU (Challenges of the Knowledge Society)
In a world were consumer is attacked by information and the decisional process is hampered by the multitudine of choices, the consumption can be explained through a multidisciplinary approach that can integrate also the economic and psychological variables. People are faced with having to choose one option out of many desirable choices, thus their options are evaluated in terms of missed opportunities instead of the opportunity's potential. In this playground appears the regret aversion that can paralyze the action of the consumer and recreate the frame in which this acts. That is why, this area has been approached through a multidiciplinary perspective that can explain better the decisional process of the buyer that can act also in a subjective and non-linear way ante and post-factum decision making.